This question already has an answer here:

If $F=0$, $F=ma \implies m\frac{(v-u)}{t}=0\implies v-u=0 \implies v=u $

Which is essentially Newton's first law.


marked as duplicate by ACuriousMind, Community Jun 3 '16 at 13:56

This question has been asked before and already has an answer. If those answers do not fully address your question, please ask a new question.


ACuriousMind's link gives you the correct answers.

But here is an additional side-note to be considered:

$$a= \frac{v-u}{t}\;;$$

Hmm; this is not true in general.

What you would want to say is that

$$F~=~ m\frac{\mathrm dv}{\mathrm dt} = ma~=~0$$

However, that doesn't mean that the body has constant velocity; for in some cases

$$\dot a ~\ne~ 0\;.$$


Not the answer you're looking for? Browse other questions tagged or ask your own question.